Insufficiency fracture of the tibial plateau after anterior cruciate ligament reconstructive surgery: a case report and review of the literature - Wong, Jessica J. (Canadian Chiropractic Association, 2013)
Peri-articular fractures after anterior cruciate ligament (ACL) reconstructive surgery are rare. To our knowledge, this case documents the first insufficiency fracture of the tibial plateau after ACL reconstruction, which presented three weeks after the procedure. A 25-year-old female recreational soccer player suffered an insufficiency fracture of the tibial plateau, extending 1.5 mm into the anterior wall of tibial tunnel and medial compartment under the anterior horn of medial meniscus, which presented as a diagnostic challenge. Clinically, the fracture mimicked a low-grade infection of the surgical site, while radiographically, the fracture resembled an avulsion fracture, later confirmed as a tibial tunnel fracture with computed tomography. With the ACL graft integrity not in jeopardy, four weeks of non-weightbearing and a delayed post-operative rehabilitation program was effective in allowing the fracture to heal. Good functional outcome was achieved after conservative management, with minimal loss of terminal knee extension and minimal pain at 22-month follow-up.